On the Role of Cholecystokinin (CCK) in Fear and Anxiety: A Review and Research Proposal - Crespi, Francesco (Journal of Human Psychology, 2019)
Cholecystokinin (CCK) is found in high concentrations in cortical and limbic structures including the amygdala of rodents, and evidence has been gathered supporting a role for CCK in the neurobiology of anxiety. A variety of animal models have been used to study a central state of fear or anxiety, state that appears to produce a complex pattern of behaviors highly correlated with each other. It is now well established that the amygdala in particular is a critical link in the pathway through which sensory stimuli come to acquire fear evoking properties. The purpose of the proposed experiments is to study the role of the putative neurotransmitter CCK in fear and anxiety in vivo by means of a methodology coupling electrochemical and electrophysiological measurements in various brain areas. Indeed, the association of in vivo differential pulse voltammetry (DPV) with in vivo extracellular single unit recording could be able to provide concomitant physiological and neurochemical indications and to relate them to behavioral events. To further study and support the initial observations pharmacological experiments will also be performed by means of CCK receptor agonists and antagonists. This may eventually lead to development of more effective pharmacological strategies for treating clinical anxiety disorders.
Keywords: Cholecystokinin; amygdala; fear and anxiety; in vivo electrochemistry; in vivo electrophysiology